Persepsi Konsumen Terhadap Produk Private Label Perusahaan Ritel - Susianti Susianti; Amandin (Management Studies and Entrepreneurship Journal (MSEJ), 2019)
The purpose of the research to determine consumer perceptions of private label products Indomaret compared with similar products from national brands in Indomaret Prabumulih. This study examined three independent variables, namely the element of private label brand awareness (X1), the perception of the quality of the product (X2), the perception of value (X3) which may affect the dependent variable. The method used in the sampling in this study is the sampling method accidental (accidental sampling. Determination of the area of ??research done intentionally (purposive) in Indomaret Prabumulih South Sumatra. The results of test f show obtained probability (Sig) is 0,000. Because the value Sig <0.05 (0.000 <0.05), then the decision is H0 rejected and Ha accepted. her significant conclusion means that, brand awareness, perceived quality and perceived value products together or simultaneously to significantly influence consumer perceptions of products private label on Indomaret Prabumulih. Then compare the value of F with Ftabel from the above table it is known that the value Fhitung 68.535. Therefore we can conclude that F count> F table (68.535> 2.70), meaning that brand awareness, perceived quality and perceived value products together or simultaneously significant effect on consumer perception on the I ndomaret Prabumulih. The hypothesis is accepted. Keywords: Brand Awareness, Perceptions of Product Quality, Perceived Value and Consumer perception, Private Label.